0072 A Chronic Animal Model to Study the Neuromechanisms that Control Hypoglossal Motoneuron Activity during Hypoxic REM Sleep. (27th April 2018) - Xi, M; Fung, S J; Chase, M H
Abstract: Introduction: There is significant controversy regarding the mechanisms that are responsible for the control of hypoglossal motoneurons during REM sleep in normal states and those that are operative during sleep disorders. Based on the previous data, we hypothesized that during REM sleep under hypoxic conditions, such as those that arise during obstructive sleep apnea (OSA), disfacilitation in addition to postsynaptic inhibition, are responsible for the depression of hypoglossal motoneuron activity. Accordingly, we developed an animal model of hypoxia in the chronic cat preparation to evaluate this hypothesis. Methods: Adult cats were prepared for monitoring behavioral states and for intracellular recordings from hypoglossal motoneurons. A chronic breathing mask was placed over the animal's nose and mouth. The oxyhemoglobin saturation level (SpO2 ) and heart rate were continuously monitored with a SurgiVet pulse oximeter. Hypoxia was induced by a ventilatory system that controls "on" and "off" flows of nitrogen gas and air into the mask. Results: In chronically-instrumented, unanesthetized cats, single and recurrent periods of hypoxia of different duration, frequency of episodes and severity (e.g., 75% SpO2 level) were successfully generated and maintained during naturally-occurring behavioral states of REM sleep, NREM sleep and wakefulness. In addition, the animals, after adaptation, exhibited spontaneous periods of sleep and wakefulness under hypoxic conditions with no significant change in sleep pattern. Conclusion: The present study demonstrates the feasibility of studying the effects of hypoxia in chronic unanesthetized cats that exhibit naturally-occurring states of sleep and wakefulness. We believe that this in vivo animal model of hypoxia, combined with intracellular recording techniques, can be utilized to study the synaptic mechanisms and neurotransmitters that control hypoglossal motoneuron activity during REM sleep under normal as well as pathological conditions, such as OSA. Support (If Any): NS094062